The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10217407
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Evaluation of Effective Properties of Randomly Distributed Gas Diffusion Layer (GDL) Tissues with Different Compression Ratios

Abstract: The gas diffusion layer (GDL) typically consists of a thin layer of carbon fiber paper, carbon cloth or nonwoven and has numerous pores. The GDL plays an important role that determines the performance of the fuel cell. It is a medium through which hydrogen and oxygen are transferred and serves as a passage through which water, generated by the electrochemical reaction, is discharged. The GDL tissue undergoes a compressive loading during the stacking process. This leads to changes in fiber content, porosity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The pores are formed as a result of extracted pores agents; therefore, the morphology and quantity of pore agents indirectly impact the physical properties of porous material. The PST approach can produce spherical, interconnected pores with a wide range of sizes [ 1 ].…”
Section: Fabrication Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pores are formed as a result of extracted pores agents; therefore, the morphology and quantity of pore agents indirectly impact the physical properties of porous material. The PST approach can produce spherical, interconnected pores with a wide range of sizes [ 1 ].…”
Section: Fabrication Technologiesmentioning
confidence: 99%
“…Fuel can be H 2 or alcohol, to name a few. The hydrogen is diffused into the anode catalyst from the gas diffusion layer where the oxidation reaction occurs, while on the other end, oxygen is reduced with the same pattern [ 1 , 2 , 3 ]. The cathode and anode reactions are as Anode: H 2 → 2H + + 2e − Cathode: O 2 + 4H + + 4e − → 2H 2 O …”
Section: Introductionmentioning
confidence: 99%
“…They found that the effective gas diffusion coefficient decreased with increasing compression ratio while the effective thermal conductivity and electrical conductivity increased. Lee et al [ 38 ] revealed that the variation of fiber volume fraction with compression ratio has a large effect on the longitudinal elastic modulus. The effect of compression on tortuosity and permeability in the in-plane and through-plane directions of GDLs was investigated by Froning et al [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 8 studied the stress− strain relationship of GDL from the perspective of solid mechanics and found that as the acting pressure is increased, the average porosity of carbon paper decreases, and the nonuniformity of porosity along with the through-plane direction increases. Lee et al 9 simulated the compression during the GDL stacking process and predicted the equivalent properties according to the change of GDL carbon fiber content, matrix content, and pore porosity. Lee et al 10 studied the effects of the material model of the membrane and thickness of the GDL on the deformation of the GDL and found that the shape and magnitude of the contact pressure at the interface are affected not by the type of the membrane material but by the selection of GDL thickness.…”
Section: Introductionmentioning
confidence: 99%